The Influence of Product Knowledge, Workload, and Work-Life Balance on the Service Performance of Frontliners at PT Bank Tabungan Negara (Persero) Tbk Bali Region - Belinda Sylvia Jaya; Trianasari; I Nengah Suarmanayasa (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of several variables, namely: (1) product knowledge, (2) workload, and (3) work-life balance on the service performance of frontliners at PT Bank Tabungan Negara (Persero) Tbk Bali Region. The population in this study consisted of all frontliners of PT Bank Tabungan Negara (Persero) Tbk Bali Region totaling 68 employees. The sampling technique used in this study was saturated sampling or total sampling, which is a sampling method in which all members of the population are used as research samples. Data in this study were collected through questionnaires and documentation. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS 29 software. The analysis included validity testing, reliability testing, classical assumption testing, partial testing (t-test), simultaneous testing (F-test), and coefficient of determination (R²). The results of the study showed a constant coefficient of 10.470, a Product Knowledge regression coefficient of 0.369, a Workload regression coefficient of -0.181, and a Work-Life Balance regression coefficient of 0.340. The results also showed that product knowledge had a positive and significant effect on frontliner service performance, workload had a negative and significant effect on frontliner service performance, and work-life balance had a positive and significant effect on frontliner service performance. Simultaneously, product knowledge, workload, and work-life balance had a significant effect on the service performance of frontliners at PT Bank Tabungan Negara (Persero) Tbk Bali Region.